Characteristics of bottom sediments (Aquasoils) of the Baklan and Boisman bays of Peter the Great Bay - Brikmans, Anastasia; Nesterova, Olga; Dmitrenko, Galina; Bovsun, Mariia (Edelweiss Applied Science and Technology, 2025)
The allocation of aquatic soils, their revision, and the collection of new data are urgent tasks in light of global challenges related to assessing the distribution and reserves of organic carbon and nutrients in the oceans, as well as managing blue carbon. This article presents the results of an assessment of the main biogeochemical parameters of the surface-active layer of bottom sediments (aquasoils) in the Baklan and Boisman bays of Peter the Great Bay in the Sea of Japan. Samples for the study were taken from the upper 5 centimeters of bottom sediments. These aquasoil samples were obtained during an expedition conducted by the scientific research vessel "Professor Gagarinsky" using geological coring techniques. The studies revealed that the content of key elements constituting the organic carbon in the bottom sediments—such as carbon, nitrogen, and phosphorus—is correlated with the silty fraction. Additionally, freshwater inflow into the bays influences the acid-base properties and geochemical composition of the bottom sediments at depths reaching up to 60 meters.